Using management by objectives as a performance appraisal tool for employee satisfaction - Xhavit Islami; Enis Mulolli; Naim Mustafa (Future Business Journal, 2018)
This study deals with the importance of applying Management by Objectives (MBO) method, as a method for performance appraisal (PA) in enhancing employees' effectiveness. A self- administered questionnaire was used, the number of participants included the survey is 172 employees from 13 firms operating in Kosovo. The study aim is to identify the importance of creating objectives, communication objectives, planning goals, setting control points, employees' commitment to determine objectives, freedom and independence in fulfilling duties, continuous communication, as steps for realizing MBO method in employees' effectiveness. The questionnaire of the study has been prepared, the responses obtained, the econometric model is constructed in order to test empirically this relationship, passed through the IBM SPSS v.23.0 program has been utilized for the obtained findings. Results and proposals are brought forward by the matched t-test, independent sample t-test, anova, pearson and correlation used as the hypothesis tests. Econometric results suggested that MBO method should be used as a method of performance appraisal as the employees' effectiveness is enhanced. Also it resulted that the evaluation of individual employees' performance and a clear definition of results are the hugest parameters from all the other activities of MBO method which we took in the study to raise employees' effectiveness in organization.
Keywords: 650; Employee effectiveness; Management by Objectives; Method; Performance appraisal; Productivity